Essentials of criminal psychology (a psychological perspective in criminology) - Manwong, Rommel K.; Pelayo, Jose Maria G. III (Wiseman's Book Trading, Inc., 2014)
"This textbook are designed to allow the end users, specifically students in criminology and psychology, to fastly comprehend criminal psychology of its general perspective. There are five (5) chapters or (5) five major topics which are boiled down on the essential areas of interest in psychology as applied in understanding crimes, criminals, and the application of psychology in law enforcement."--Preface